An evaluation of the dot-ELISA procedure as a diagnostic test in an area with a high prevalence of human Toxocara canis infection - Bojanich, María Viviana (2012)
Fil: Bojanich, María Viviana. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.